Contribution of Ruminal Bacteriome to the Individual Variation of Nitrogen Utilization Efficiency of Dairy Cows - Li, Min; Zhong, Huiyue; Li, Ming; Zheng, Nan; Wang, Jiaqi; Zhao, Shengguo (Frontiers in Microbiology, 2022)
High nitrogen utilization efficiency (NUE) is important for increasing milk protein production, decreasing the feed nitrogen cost and nitrogen emission to the environment. Currently, there is limited whole picture of the relationship between ruminal bacteriome and NUE of dairy cows, even though some information have been revealed about the bacteriome and milk or milk protein production of dairy cows. The purpose of this study was to compare the rumen bacterial community in dairy cows with different nitrogen utilization efficiency under the same diet. The natural abundance of 15N between the animal proteins and diet (Δ15N) was used as a simple, noninvasive and accurate biomarker for NUE in ruminants to mark the individual variation. Dairy cows with high NUE (HE_HP, n=7), medium NUE (ME_MP, n=7) and low NUE (LE_LP, n=7) were selected from 284 Holstein dairy cows with the same diet. Measurement of the rumen fermentation indices showed the proportion of propionate was higher in HE_HP cows and ME_MP cows than LE_LP cows (P<0.05). The diversity of rumen bacterial community was higher in LE_LP cows than ME_MP cows and HE_HP cows by 16S rRNA sequencing analysis (P<0.05). Moreover, at the genus level, the relative abundances of Succinivibrionaceae_UCG_001, uncultured_Selenomonadaceae and Acidaminococcus were higher in HE_HP cows than LE_LP cows (P<0.05). Interestingly, we found these bacteria were positively correlated with milk protein yield, and negatively correlated with Δ15N (P<0.05). However, Clostridia_UCG_014, Saccharofermentans, Bacilli_RF39, Desulfovibrio were lower in HE_HP cows and ME_MP cows than LE_LP cows (P<0.05), which were negatively correlated with milk protein yield, and positively correlated with Δ15N (P<0.05). In conclusion, the study showed that the diversity and relative abundances of rumen bacteria differed among different NUE cows, indicating that rumen bacteriome contributes to nitrogen metabolism in dairy cows.